2008
DOI: 10.1097/mcp.0b013e3283043e1b
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse pulmonary ossification: an unusual interstitial lung disease

Abstract: Diffuse pulmonary ossification is still underrecognized during life. Its relevance concerning the increasing age of population and longer survival of patients with chronic diseases is underrated. A timely diagnosis will enable a better understanding of pathogenesis and natural course of disease thus paving the way to new therapeutic strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 16 publications
4
40
0
1
Order By: Relevance
“…Saks et al reported a case of DPO detected using bone scanning with Tc-99m hydroxymethylene in 1984 (8). However, it has also been reported that Tc-99m hydroxymethylene is less sensitive in the nonextensive stage (2). In this case, the laboratory findings showed slight elevations of urinary deoxypyridinoline and serum I-CTP, which usually imply the predominance of bone resorption.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Saks et al reported a case of DPO detected using bone scanning with Tc-99m hydroxymethylene in 1984 (8). However, it has also been reported that Tc-99m hydroxymethylene is less sensitive in the nonextensive stage (2). In this case, the laboratory findings showed slight elevations of urinary deoxypyridinoline and serum I-CTP, which usually imply the predominance of bone resorption.…”
Section: Discussionmentioning
confidence: 74%
“…DPO is usually associated with cardiovascular or respiratory disease. Therefore, the number of idiopathic cases is very small (1)(2)(3)(4). We herein present an idiopathic case of DPO detected during a routine health examination.…”
Section: Introductionmentioning
confidence: 99%
“…Nodular pulmonary ossification has been associated with chronically elevated central venous pressure and is thought to be due to hemosiderin deposition within the alveoli due to chronic vascular congestion. 5,6 Dendriform pulmonary ossification has been most associated with pulmonary fibrosis [7][8][9] and is thought to result from recurrent lung injury with resulting calcium deposition due to inflammatory cytokines and an alkaline environment. 5 Tissue sampling with pathologic evaluation provides the definitive means for diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Few studies have been devoted to the treatment of this disorder. Low calcium diet, calcium-binding drugs, and corticosteroids, all failed to show effectiveness for decreasing calcium deposition within the lungs because of various underlying conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1,5 Other influences, such as angiogenesis, chronic venous congestion, and abnormal mineral metabolism, may play a role as well. 1,5,6 There are two types of ossification, localized and diffuse. The localized type refers to focal deposition of bone within or adjacent to lung tissue injured by any kind of disease process, mainly including lung abscess, tuberculosis and other infectious, or parasitic diseases, trauma, primary tumors, and metastatic cancer.…”
Section: Authors' Commentmentioning
confidence: 99%